Pengaruh Fitur Paylater dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa Akuntansi - Putra, Tri Arya; Sunarmi, Sunarmi (Journal of Business and Economics Research (JBE), 2024)
This research aims to analyze the influence of paylater features and financial literacy on the consumptive behaviour of accounting students in Java and Sumatra. The method used is quantitative with a cross-sectional approach. Sample determination using purposive sampling technique. Primary data collection in the form of a Likert scale questionnaire distributed to respondents via Google-form totalling 396 accounting students in Java and Sumatra. Data analysis was performed using ordinal logistic regression in using the SPSS version 25.0 programme. The results of the wald test calculation on the Paylater Feature variable (X1) the coefficient value of the paylater feature is -3.035 in category 1 and -1.197 in category 2, and the significance value of both categories is 0.000 0.05 and category 2 is 0.760> 0.05, meaning that Financial Literacy has no effect on the Consumptive Behaviour of Accounting Students.